G227 Rituximab in, frequently relapsing/steroid dependent nephrotic syndrome: does the dose matter?. (May 2019) - Webb, H; Yu-hin Chan, E; Tullus, K
Abstract : Background: Rituximab (RTX) is a commonly used and effective treatment in frequently relapsing/steroid-dependent nephrotic syndrome (FR/SDNS) in children. Data regarding the most effective dosing regimen are however limited. Methods: We conducted a multi-center retrospective cohort study at 11 centers in Asia, Europe and North America. Children and young people with complicated FR/SDNS receiving RTX and followed for at least 18 months from 2005–2016 were recruited. Three dosing regimens: low (375 mg/m2), medium (750mg/m 2 ) and high (1125–1500 mg/m2), and effect of concomitant immunosuppression (IS) were examined. Kaplan-Meier analysis and Cox regression were used to evaluate factors associated with relapse. Results: We analyzed 517 patients (mean age 11.2±4.0, 67.3% boys), of whom 193, 212 and 112 were given low, medium and high dose, respectively. Proportions of children with sustained long-term remission at 12, 18 and 24 months were similar among the regimens. 58.2% children discontinued all co-medications. Median relapse-free survival of low, medium and high dose were 11.7, 11.9 and 13 months, respectively (p=0.42). When IS was taken into the analyses, relapse-free survival of the regimens was different between the Kaplan Meier Curve (p=0.005). Risk of relapse in children who had been given high dose RTX without IS and children given all RTX regimens with IS were significantly lower than in those given the low RTX dose without IS. Adjusted hazard ratios (HRadj ) ranged from 0.33 to 0.44 ( p s <0.008). Conclusion: Rituximab dose and use of concomitant IS hade important effects on the long-term control of complicated FR/SDNS. Children given the low dose of RTX without IS had a shorter relapse-free survival than the other children.